Novelty in patents: a European perspective - Atkinson, Jonathan D.M. (Henry Stewart Talks, 2019)
What makes an invention patentable, Novelty and jurisdiction, State of the art, UK & EU practice through examples, Prior rights, Non-prejudicial disclosures, Practical points, Enabling disclosures, Disclaimers in novelty, Generic vs. Specific, Selection inventions, First & further medical use of known compound, Patent specification